Religion in cathedrals: pilgrimage, heritage, adjacency, and the politics of replication in Northern Europe. Issue 1 (2nd January 2019) - Coleman, Simon; Bowman, Marion
ABSTRACT: Much of this thematic issue emerges from work carried out for an AHRC-funded project, Pilgrimage and England's Cathedrals, Past and Present Cathedrals (PEC). In this introduction, we explore the possibilities of developing a new sub-field oriented around exploring the shaping of belief and praxis in and by cathedrals. After noting the renewed popularity of these institutions in England, we provide a brief history of cathedrals within and beyond Europe, highlighting both particular periods of expansion and pilgrimage practices relating to them. We emphasize the significance of cathedrals in juxtaposing 'sacred space' with 'common ground.' This approach is complemented by a focus on how cathedrals both embody and encourage material and liturgical forms of 'replication'—a theme that provides a useful comparative approach for historians and ethnographers alike. Potential for future research is also briefly discussed.